Análise da confiabilidade de vigas de concreto armado com plástico reforçado por fibras - Sidnea Eliane Campos Ribeiro (2009)
Recent years have seen a growing interest for high performance materials such as concrete and high strength composite materials, among others. This interest aims to obtain higher resistance and greater durability, and therefore potential gains to the costs over the life of the structure. A major problem associated with the durability ofreinforced concrete is the corrosion of reinforcement steel. Thus the plastic reinforced by fiber (FRP) provides a promising prospect for use as reinforcement for reinforced concrete. Although the use of FRP as structural reinforcement can show great promise in terms of durability, the particular characteristics of this material have led to new challenges in the design of structural components in reinforced concrete with FRP (FRP-RC). Some design recommendations have been developed; they have in common the fact of being based on existing recommendations for traditional steel reinforced concrete (RC). In the design of RC beams, failure is dictated by the yielding of steel, resulting in a ductile failure. In the case of FRP-RC beams, involving two fragile materials, a fragile failure is inevitable. Thus, a change in the RC beam design paradigm (underreinforced beams) is necessary. Therefore, due to increased use of FRP and also the differences between the two materials (steel and FRP), the reliability of FRP-RC beams shall be evaluated. Most of the suggestions proposed for the design of FRP-RC beams is based on a deterministic point of view. However, since most of the variables involved in the project (mechanical properties, geometric characteristics, loads, etc.) is random, in this work, methods of structural reliability, i.e., probabilistic methods are used to assess the reliability of FRPRC beams. Monte Carlo simulation is used in the computation of the probability of failure of 81 FRP-RC beams designed according to ACI-440 (2006). The effect of